2018
DOI: 10.1007/s00220-018-3160-6
|View full text |Cite
|
Sign up to set email alerts
|

Positive Definite Functions on Coxeter Groups with Applications to Operator Spaces and Noncommutative Probability

Abstract: A new class of positive definite functions related to colour-length function on arbitrary Coxeter group is introduced. Extensions of positive definite functions, called the Riesz-Coxeter product, from the Riesz product on the Rademacher (Abelian Coxeter) group to arbitrary Coxeter group is obtained. Applications to harmonic analysis, operator spaces and noncommutative probability is presented. Characterization of radial and colour-radial functions on dihedral groups and infinite permutation group are shown.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Apparently no version of Drury's theorem is known for these notions in non-abelian groups. We refer to Bożejko and Speicher's [6] and also the recent work [5] for some results on completely positive functions on Coxeter groups that may be related to our own. See also [4].…”
mentioning
confidence: 87%
“…Apparently no version of Drury's theorem is known for these notions in non-abelian groups. We refer to Bożejko and Speicher's [6] and also the recent work [5] for some results on completely positive functions on Coxeter groups that may be related to our own. See also [4].…”
mentioning
confidence: 87%
“…In [11] it is proved that the generators in any Coxeter group satisfy the weak Sidon property and the preceding remark is explicitly applied to that case.…”
Section: λ(P)-setsmentioning
confidence: 99%
“…They showed that it implies that infinite Coxeter groups do not have Kazhdan's property (T ). This result was further generalized to multi-parameters [BS03] and also other variants of the Coxeter function (colour-length) were studied [BS96,BGM18]. All the considered functions share two distinctive features: (I) they are positive definite on the continuos set −1 ≤ q ≤ 1, (II) they are not (generically) invariant by conjugation.…”
Section: Introductionmentioning
confidence: 96%
“…Note that the set of parameters for which the signed reflection function is positive definite is a discrete set (except the degenerate case q + = 0), which confirms that the behaviour of the reflection function is very different then its Coxeter counterpart and that the properties (I) and (II) are correlated. Another difference is visible in the strong correlation between parameters q + and q − , while the parameters in the multivariate versions of the Coxeter function studied in [BS03,BGM18] can take any value in the interval [−1, 1] independently. The methods used in the previously mentioned works on the Coxeter functions are not applicable here and our approach is based on the connection between the representation theory of the hyperoctahedral group and symmetric functions.…”
Section: Introductionmentioning
confidence: 99%